Variability in Early Post-main-sequence Stars in Globular Cluster NGC 3201 - D. Ulloa-Solís; C. C. Cortés; S. Villanova; Á. Llancaqueo Albornoz; J. A. Ahumada; C. Parisi (The Astronomical Journal, 2023)
In this paper we study stellar variability in the globular cluster NGC 3201 in the magnitude range V = 16–17, corresponding to the subgiant branch and blue stragglers region of the cluster. Our aim is to expand the sample of new type of variables with low amplitude and a short period found in previous papers. We used observations obtained at the Complejo Astronómico El Leoncito. We applied statistical tests and analyzed periodograms obtained by generalized Lomb–Scargle and phase dispersion minimization methods. We found five stars considered as variables and one as a possible variable. According to their periods (fluctuating between 0.33 and 0.57 days), amplitudes (between 0.03 and 0.87 V magnitudes), the position in the color–magnitude diagram, and the shape of their phased light curves, they do not resemble any known variable star. Because stellar variability could be produced by more than one process, we propose to complement this work with a spectroscopic analysis to confirm our results.